The Correlation of Arm Muscle Power and Flexibility Of the Waist to the Field Tennis Service Capability. - Rices Jatra; Ricky Fernando; Raffly Henjilito; Mhd Ikhsan Trianda (Performa, 2022)
The purpose of this study was to determine the contribution of arm muscle power and flexibility to the ability of field tennis service. The type of this research is correlation. The population and sample in this study were local 3rd semester 3 c Physical Education Teacher Training Offices of UIR, totaling 23 people. The research instruments used were overhead medicine ball throw tests, flexibility tests, and field tennis service tests. The data analysis technique used is to calculate multiple correlation values. Based on the results of the study showed that there was a contribution of arm muscle power and flexibility to the results of the ability to service tennis tennis students with a calculated value = 0.698.